Development and Evaluation of Nursing User Interface Screens Using Multiple Methods - Hyun, Sookyung (2009)
Building upon the foundation of the Structured Narrative electronic health record (EHR) model, we applied theory-based (combined Technology Acceptance Model and Task-Technology Fit Model) and user-centered methods to explore nurses’ perceptions of functional requirements for an electronic nursing documentation system, design user interface screens reflective of the nurses’ perspectives, and assess nurses’ perceptions of the usability of the prototype user interface screens. The methods resulted in user interface screens that were perceived to be easy to use, potentially useful, and well-matched to nursing documentation tasks associated with Nursing Admission Assessment, Blood Administration, and Nursing Discharge Summary. The methods applied in this research may serve as a guide for others wishing to implement user-centered processes to develop or extend EHR systems. In addition, some of the insights obtained in this study may be informative to the development of safe and efficient user interface screens for nursing document templates in EHRs.